Holistic management of a 51-year-old male patient with multibacillary hansen's disease through a family doctor approach - Pratiwi Hesti Harmoni; Hidayatul Musabakoh (Institute of Computer Science (IOCS), 2026)
Hansen's disease, or leprosy, is a chronic progressive granulomatous disease caused by Mycobacterium leprae, which primarily affects the skin and peripheral nervous system. This disease remains a public health problem in several regions of Indonesia, including Grobogan Regency. The prevalence rate of leprosy in Grobogan Regency in 2022 was 3 per 100,000 population, and the incidence rate of new cases was 0.7 per 100,000 population. This case report aims to apply the principles of family medicine in the holistic and comprehensive management of leprosy patients, with a patient-centered and family-oriented approach, based on evidence-based medicine. This report uses a case study approach. Primary data were obtained through anamnesis, physical examination, and home visits to evaluate the patient's living environment. The evaluation was conducted comprehensively through a holistic diagnostic approach, covering the initial phase (assessment), the intervention process, and the results. The management of leprosy with a holistic and evidence-based family medicine approach can provide more optimal results, not only in clinical aspects but also in improving the understanding and involvement of patients and their families. This approach supports efforts to prevent disability and improve the overall quality of life of patients.